«Buenas tonterías dicen los que estudian». The conferences in the agricultural education law of 1876 as a tool for rural transformation - Gómez-Martín, María; Copena Rodríguez, Damián (Historia y Política, 2025)
On 1 August 1876, the Law on Agricultural Education was passed. This law was intended to modernise the situation of the primary sector through the instruction of the Spanish peasantry. To this purpose, the Law deployed a wide range of initiatives, among which was the holding of a lecture with agrarian content every Sunday in all the town halls of the country. The aim of this text is to analyse the process of creation and implementation of the agricultural conferences developed under this Law. For this reason, it has been necessary to use various sources, especially primary documentation in archives and newspaper and periodical publications. The article presents the course of this initiative, which essentially took place over four academic years, between 1876 and 1880, showing the difficulties encountered in the implementation of an extremely ambitious experience, as well as the successes obtained during the process.